Discussing Virtual Tools That Simulate Probabilities: What are the middle school teachers’ concerns? - Savard, Annie; Freiman, Viktor; Theis, Laurent; Larose, François (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
Mathematics teachers, researchers and specialists in educational technology from Quebec, Canada developed virtual tools that make interactive simulations of games of chance. These tools were presented to a group of teachers from New Brunswick through workshops and they then got to test and validate them with their students. Semi-structured interviews were conducted with groups of teachers following the experimentation with the tools. Results show an appreciation of the rich educational potential the virtual tools bring and the pedagogical scenarios that come with them. Participants suggest that working with simulators would increase students’ motivation and deepen their conceptual understanding of concepts that are otherwise hard to grasp. But they, however, lack professional development on how to teach probability and need techno-pedagogical and didactical follow-ups.